2015
DOI: 10.1108/ijopm-02-2014-0089
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical perspectives in operations management: an analysis of the literature

Abstract: Purpose – It is important to advance operations management (OM) knowledge while being mindful of the theoretical developments of the discipline. The purpose of this paper is to explore which theoretical perspectives have dominated the OM field. This analysis allows the authors to identify theory trends and gaps in the literature and to identify fruitful areas for future research. A reflection on theory is also practical, given that it guides research toward important questions and enlightens OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 69 publications
2
84
1
1
Order By: Relevance
“…In fact, PM is not only a set of interrelated processes (Neely et al 2002). Rather, it serves as 'a linguistic device used to organize a complex empirical world' (Bacharach 1989, p. 496) as cited in (Walker et al 2015(Walker et al , p. 1183 As further elaborated in the methods section, our research process started off with queries aimed at understanding differences between organizational and interorganizational PM. 1 This conceptual paper seeks to contribute to this challenge, based on a review of interorganizational cooperation and PM literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PM is not only a set of interrelated processes (Neely et al 2002). Rather, it serves as 'a linguistic device used to organize a complex empirical world' (Bacharach 1989, p. 496) as cited in (Walker et al 2015(Walker et al , p. 1183 As further elaborated in the methods section, our research process started off with queries aimed at understanding differences between organizational and interorganizational PM. 1 This conceptual paper seeks to contribute to this challenge, based on a review of interorganizational cooperation and PM literature.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model we seek to develop does not represent a theory in the sense of offering a validated explanation of a phenomenon as common in the natural sciences. Rather, it serves as 'a linguistic device used to organize a complex empirical world' (Bacharach 1989, p. 496) as cited in (Walker et al 2015(Walker et al , p. 1183 As further elaborated in the methods section, our research process started off with queries aimed at understanding differences between organizational and interorganizational PM. Key authors in the field were identified; highly cited research was looked up using academic and publishers' databases.…”
Section: Introductionmentioning
confidence: 99%
“…Eisenhardt, 1989;Ketokivi and Choi, 2014;Walker et al, 2015). Theory elaboration was used because this research focuses on a contemporary phenomenon, i.e.…”
Section: Research Approachmentioning
confidence: 99%
“…We need to make sure that all progress in operations management theory leads to research that is both scientific and relevant [Walker et al, 2015].…”
Section: Conclusion and Future Directions Of Researchmentioning
confidence: 99%